Interferensi sampel lipemik pada bayi dengan lipemia retinalis dikarenakan primary mixed hyperlipidemia: laporan kasus - Andi Munawirah; Habibah S. Muhiddin; Liong Boy Kurniawan; Ruland DN Pakasi (DiscoverSys Inc., 2019)
Background: Interference is a condition of which sample components cause an error in the analyte measurement in the analyzer.Â The most common cause of interference is lipemic sample. Lipemic sample is characterized by turbidity of the serum or plasma caused by an accumulation of lipoprotein particles. Primary mixed hyperlipidemia (PMH) is a cause of primary hypertrigliseridemia with lipemia manifestation.Case report: A three month-old baby boy was admitted to a hospital, having white spots in his black eyes. The spots were seen clearer at light exposure, and ophthalmologic examination indicated lipemia retinalis. Patientâ€™s sample was lipemic and its laboratory analysis resulted in as follow: WBC 13.103/Î¼L, Hb 15.6 gr/dL, RBC 2.99 106/Î¼L, triglyserida 10.435 mg/dL, total cholesterol 631 mg/dL, HDL 12 mg/dL, LDL 195 mg/dL, and apoprotein B 196 mg/dL. Due to a significant interference, SGOT, SGPT, ureum and creatinin were not obtained. Immunologic serum analysis of the patient and his mother showed an increasing of antibody IgG CMV: 28 dan 20 IU/ml, respectively.Conclusion: Lipemic samples could directly affect most of laboratory examination methods. Laboratory results with such lipemia interferences shoud be interpretated critically and accurately to produce precise diagnosis, and in turn, monitoring of patient with lipemia.